Análises das barreiras percebidas para a prática de atividade física de idosos no meio rural e urbano do município de Santa Maria, RS - Lameira, Fernanda Rossatto (2018)
Aging is a natural process in which various changes occur in the body and in people's lifestyles. These variations are derived from numerous factors such as socioeconomic conditions and chronic diseases. The environment in which the elderly live is also one of the factors that influence lifestyle and interfere with the course of aging. Considering the differences between localities and the high rate of inactivity in old age, this study aims to analyze the main barriers perceived by elderly people, from rural and urban areas, to practice physical activity. The approach was made through home visits in three urban districts and three rural districts, with different socioeconomic levels (high, medium and low incomes). To evaluate the barriers, a questionnaire was applied that evaluates the perceived barriers to the practice of physical activity. The comparisons between the groups and the barriers were performed by the Chi-square test (CHI²). Participants were 208, of which 141 were urban and 67 were rural. The majority of the individuals surveyed are female and married, with a mean age of 70.34 ± 7.86 years, and on average presented a high BMI (29.71 ± 5.29), accusing excess weight, mainly between the women. The most cited perceived barrier was the lack of companionship to practice physical activities, followed by having some disease or injury that interferes in practice. When comparing the barriers between the sexes and the localities, there was a significant difference in the barrier "feel lazy or tired to do physical activity" with urban women being the most cited (20.7%), and barrier 2 "having some injury or illness that interferes with physical activity "was also more cited by women (29.3%) than by men (12.5%). It is concluded that the prevalence of perceived barriers to the practice of physical activity in the elderly interviewed is high, especially the fact that there is no company to practice physical activities. Possessing some illness or injury that interferes in practice was the second most reported barrier by most of the elderly in both locations.